Fe2Mn(μ3‐O)(COO)6 Cluster Based Stable MOF for Oxidative Coupling of Amines via Heterometallic Synergy. Issue 11 (24th August 2021) - Wang, Ying‐Xia; Wang, Hui‐Min; Meng, Pan; Song, Dong‐Xia; Qi, Zhikai; Zhang, Xian‐Ming
Main observation and conclusion: The direct catalytic oxidative coupling of amines is one of the attracting methods for the synthesis of a variety of pharmaceutical or industrial needed imines. Numerous earth‐abundant manganese based salts, oxides, and complexes have been applied in this reaction. However, these compounds suffered from difficult separation, large catalyst loading, complicated reactivation or indeterminate activity. Considering the facts that metal‐organic frameworks (MOFs) with crystalline structure, precise composition, and enormous surface area have superior performance in heterogeneous catalytic reactions, herein, we introduced Mn into [Fe3 ( μ 3 ‐O)(CH3 COO)6 ], one of the precursors for the preparation of stable MOFs, and got [Fe2 Mn( μ 3 ‐O)(CH3 COO)6 ] cluster. After ligand replacement with biphenyl‐3, 4', 5‐tricarboxylic acid (BPTC), heterometallic cluster‐based [Fe2 Mn( μ 3 ‐O)(BPTC)2 (DMF)2 (H2 O)] (1) was obtained. As expected, 1 is stable and able to catalyze the homo‐ or cross‐coupling of amines effectively and selectively with 0.9 mol% catalyst loading at room temperature. Control experiments indicated that the catalytic activity of 1 mainly stems from Mn sites and that Fe synergistically contributes to the stability. Additionally, 1 is recyclable and can be reused easily for at least 8 runs without obvious decrease in catalytic ability. To our knowledge, 1 should be the first heterometallic cluster‐based MOF with defined structure suitable for the synthesis of diverse imines from oxidative coupling of amines under mild conditions, which may shed light on the easy preparation of effective heterogeneous catalysts for organic synthesis. Abstract : Catalytic active Mn was introduced into stable Fe2 M( μ 3 ‐O) cluster based MOF and used for the oxidative homo‐ or cross‐coupling of amines with low catalyst loading, high selectivity, broad substrate, good recyclability and synergistic effect.